Inhibiting Factors for Learning from Home in Elementary School Age Children at SDN 01 Kemantren - Fariah, Aen (Devotion : Journal of Research and Community Service, 2021)
This study discusses the inhibiting factors for online learning during the Covid-19 pandemic. This study aims to make parents aware of the factors that become obstacles when accompanying their children to study from home. This type of research uses qualitative methods and empowerment activities carried out by the research team, the researcher provides an open questionnaire to the subject, namely the parents of students aged 9-10 years old. In addition, we conduct education to find solutions to the inhibiting factors while learning from home takes place online. From the results of this study, it is concluded that the parents of students have an inhibiting factor in accompanying learning from home, namely parents have difficulty understanding the material being studied by the child, which causes emotional expressions of anger, annoyance, resentment. Apart from that, the limitations of the gadgets that are owned and the signal constraints are also inhibiting factors in distance learning.